Village Government Capacity in Village Fund Budget Management in Pulau Sembilan District, Sinjai Regency - Muhammad Takdir; Andi Bahrun Syam; Sakrawandi Sakrawandi (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2021)
Rural development is a priority agenda for national development to improve the welfare of the people. The results of this study examine how the ability of the village government to utilize the village fund budget is so large, without any form of deviation. In public sector studies, capacity is defined as the ability to manage human resources, finance, physical infrastructure, and information. In this study, qualitative research methods were used to obtain accurate data and collect reliable data from related institutions and informants. The informants in the study were 7 village heads. The findings in this study are that the capacity of the village government in managing the village funds budget in Pulau Sembilan District, Sinjai Regency is not optimal